Exploring undergraduate clinical students' perspectives on interprofessional education / Nur Zainie Abd Hamid ... [et al.] - Abd Hamid, Nur Zainie; Muzaini, Azlina; Rashed@Mohamed, Abd Ghani (Universiti Teknologi MARA, Perlis, 2024)
Interprofessional Education (IPE) has been advocated to prepare future healthcare professionals for collaborative practice to improve the quality of patient care and overall health outcomes. The problem statement revolves around the need to bridge the gap between the traditional, silos education of healthcare disciplines and the demands of a modern healthcare ecosystem. Insufficient IPE can result in fragmented patient care, communication breakdowns and suboptimal outcomes. Thus, this study aimed to investigate the perceptions of undergraduate clinical students from Malaysian higher institutions about Interprofessional Education (IPE). This study was conducted among undergraduate final-year students of clinical programs, including nursing, Medical, Nursing, Pharmacy and Health Sciences programs in selected private and public Malaysian higher institutions. The quantitative data was analysed via descriptive statistics using Statistical Package for the Social Sciences (SPSS). Overall, the study received 288 responses from four public institutions and 3 private institutions. About 94.4% (272) of respondents claimed perceived needs for IPE. Most students agreed that patient care and critical patient care in general wards and community chronic patient care should be included in the content of IPE. More than 80% of the respondents agreed collaboration and teamwork, mutual understanding for other disciplines/professionals, conflict control and effective communication are the essential skills to be learned by IPE. The three most wanted IPE learning methods are lecture and discussion, clinical rotation, and role-playing. This study revealed differences in needs and perceptions regarding IPE between programs. This finding warrants further research to design appropriate IPE program goals and strategies that suit specific students' needs.